Euthanasia and organ donation still firmly connected: reply to Bollen et al - Buturovic, Zeljka (Journal of medical ethics, 2022)
Bollen et al, replying to my own article, describe, in great detail, administrative and logistical aspects of euthanasia approval and organ donation in the Netherlands. They seem to believe that no useful lessons can be drawn from experiences of related groups such as euthanasia patients (typically patients with cancer) who cannot donate organs; patients who chose assisted suicide as opposed to euthanasia; patients in intensive care units and their relatives and suicidal young people as if we can only learn about organ donation in euthanasia patients by studying this exact group and no other, no matter how closely related and obviously relevant. However, it is not only permissible but also absolutely essential to gather evidence that goes beyond immediate point of interest and carefully study groups that share important features with it. Also, groups eligible for euthanasia are constantly expanding, theoretically, legally and practically, and it would be irresponsible to not foresee what are likely future developments. Finally, myopic focus on the technicalities of the procedure misses psychological reality that drives decisions and behaviours and which rarely mimics administrative timelines. Patients proceeding through euthanasia pipeline already face substantial situational pressure and adding organ donation on top of it can make the whole process work as a commitment device. By allowing euthanasia patients to donate their organs, we are giving them additional reason to end their lives, thus creating an unbreakable connection between the two.